Oral administration of antioxidants improves skin wound healing in diabetic mice. Issue 6 (12th October 2016) - Pessoa, Ana Flávia Marçal; Florim, Juliana Costa; Rodrigues, Hosana Gomes; Andrade‐Oliveira, Vinicius; Teixeira, Simone A.; Vitzel, Kaio Fernando; Curi, Rui; Saraiva Câmara, Niels Olsen; Muscará, Marcelo N.; Lamers, Marcelo Lazzaron; Santos, Marinilce Fagundes
Abstract: Oxidative stress aggravates several long‐term complications in diabetes mellitus. We evaluated the effectiveness of the oral administration of antioxidants (vitamins E and C, 40 and 100 mg/kg b.w., respectively) on skin wound healing acceleration in alloxan‐induced diabetic mice. Mice were wounded 30 days after the induction of diabetes. Antioxidants were effective in preventing oxidative stress, as assessed by TBARS. The enzymes catalase, glutathione reductase, glutathione peroxidase, and superoxide dismutase were increased in diabetics on the 3rd day post‐wounding; catalase and glutathione peroxidase remained still augmented in diabetics after 14th day postwounding, and the treatment with vitamins restored their activities to control. After 3 days, diabetic mice showed lower infiltration of inflammatory cells (including CD11b + and Ly6G + cells) and reduced levels of KC, TNF‐α, IL‐1β, and IL‐12 p40 when compared with control mice. The treatment restored cytokine levels. After 14 days, diabetic mice showed late wound closure, persistent inflammation and delayed reepithelialization, accompanied by an increase in MIG + /CD206 − macrophages whereas CD206 + /MIG − macrophages were decreased. Cytokines IL‐12p40, TNF‐α, IL‐1β, and KC were increased and normal levels were restored after treatment with antioxidants. These results suggest that oxidative stress plays a major role in diabetic wound healing impairment and the oral administration of antioxidants improves healing by modulating inflammation and the antioxidant system with no effect on glycemia.